Modulatory Effects of Lawsonia inermis, Waltheria indica, Moringa oleifera and Nigella sativa on Haematology, Blood Pressure and Electrocardiographic Parameters of Wistar Rat Exposed to Acute Pain - Aremu Abdulfatai; Idris Fatimah Jiddah; Akorede Ganiu Jimoh; Basiru Afisu; Azeez Oyebisi Mistura (Journal of Applied Veterinary Science And Technology, 2023)
Background: Pain is an obnoxious stimulus usually triggered by stressors that can affect homeostasis. The inability to sense pain is usually connected to abnormal fluctuations in normal body functions, leading to shortened life expectancy. Purpose: This study aimed to assess the effects of Lawsonia inermis, Waltheria indica, Moringa oleifera and Nigella sativa on hematology, electrocardiography, and blood pressure in Wistar rats experimentally exposed to acute pain. Methods:21 Adult female rats were divided into (1-7) of three rats each. Group 1 (negative control), group 2 (positive control), group 3 (Lawsonia inermis at 200 mg/kg), group 4 (Waltheria indica at 200 mg/kg), group 5 (Nigella sativa at 200 mg/kg), group 6 (Moringa oleifera at 200 mg/kg), and group 7 (Diclofenac at 10 mg/kg). Rats were dosed for 14 days, after which pain was induced. Result: The extracts showed non-significant increases in most hematological parameters, including PCV, RBC, and WBC counts, compared to positive controls. The effects of the extracts on the electrocardiographic parameters were not significant. Although the extract relieved pain, the effect of acetic acid on the heart was not completely ameliorated. The results of this study showed high blood pressure in untreated rats, which could be linked to pain induction.  M. oleifera and W. indica exhibited minimal blood pressure-lowering effects. W. indica. and L. inermis showed transient blood pressure-lowering effects. Conclusion: This study concluded that the extract had a modulatory effect on hematology and a lowering effect on blood pressure and electrocardiac parameters in all treatments.